Secondary organic aerosol formation from nitrate radical oxidation of styrene: aerosol yields, chemical composition, and hydrolysis of organic nitrates - Y. Wang; Y. Wang; X. Zhang; Y. Huang; Y. Liang; Y. Liang; N. L. Ng; N. L. Ng; N. L. Ng (Atmospheric Chemistry and Physics)
Styrene is emitted by anthropogenic sources and biomass burning and is highly reactive towards atmospheric oxidants. While it has the highest nitrate radical (NO3) reactivity among aromatic hydrocarbons, the NO3 oxidation of styrene and formation mechanisms of secondary organic aerosols (SOA) have not been investigated. In this study, we conduct chamber experiments with styrene concentrations ranging from 9.5 to 155.2 ppb. The resulting SOA yields range from 14.0 % to 22.1 % with aerosol mass loadings of 5.9–147.6 µg m−3 after wall loss corrections. The chemical composition of SOA is characterized by online measurements, revealing that dimeric organic nitrates (ONs) constitute 90.9 % of the total signal of particle-phase products. C16H16N2O8 and C8H9NO4 are identified as the major particle-phase products, which constitute 88.3 % and 4.1 %, respectively, of the measured signal. We propose formation mechanisms for the ON products, including the common RO2+ RO2 /<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="539a58614ea8688159b8effbc6d3da8d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-25-5215-2025-ie00001.svg" width="8pt" height="14pt" src="acp-25-5215-2025-ie00001.png"/></svg:svg> HO2 pathway and other radical chain termination reactions such as RO + R and R + R. We also investigate the hydrolysis of particulate ONs. The hydrolysis lifetime for ONs is determined to be less than 30 min. This short hydrolysis lifetime can be attributed to the stabilization of the carbocation by delocalized π orbitals of the benzene-related skeleton of aromatic ONs. This work provides the first fundamental laboratory data to evaluate SOA production from styrene + NO3 chemistry. Additionally, the formation mechanisms of aromatic ONs are reported for the first time, highlighting that compounds previously identified as nitroaromatics in ambient field campaigns could also be attributed to aromatic ONs.